2020
DOI: 10.1111/bjh.16385
|View full text |Cite
|
Sign up to set email alerts
|

A pilot trial of complement inhibition using eculizumab to overcome platelet transfusion refractoriness in human leukocyte antigen allo‐immunized patients

Abstract: Heavily transfused patients frequently develop human leukocyte antigen (HLA) allo-immunization resulting in platelet transfusion refractoriness and a high risk for life-threatening thrombocytopenia. Data suggest complement activation leading to the destruction of platelets bound by HLA allo-antibodies may play a pathophysiologic role in platelet refractoriness. Here we conducted a pilot trial to investigate the use of eculizumab, a monoclonal antibody that binds and inhibits C5 complement, to treat platelet tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 25 publications
1
13
0
2
Order By: Relevance
“…39 The complement inhibitor eculizumab has been used to increase the CCI in a limited number of transfusion refractory patients with severe thrombocytopenia. 40 Finally, in extreme cases when a patient's count must be increased for a procedure, we have resorted to an "in vivo adsorption" strategy: If a patient has a strong antibody against HLA-A2, we repeatedly transfuse an HLA-A2 positive unit to deplete the antibody, then drip-in an A2 positive unit during the procedure.…”
Section: Other Optionsmentioning
confidence: 99%
“…39 The complement inhibitor eculizumab has been used to increase the CCI in a limited number of transfusion refractory patients with severe thrombocytopenia. 40 Finally, in extreme cases when a patient's count must be increased for a procedure, we have resorted to an "in vivo adsorption" strategy: If a patient has a strong antibody against HLA-A2, we repeatedly transfuse an HLA-A2 positive unit to deplete the antibody, then drip-in an A2 positive unit during the procedure.…”
Section: Other Optionsmentioning
confidence: 99%
“…Because destruction by complement is completely independent of FcγRs, differences in the ability to fix complement may be another explanation for the discrepancy between PLT refractoriness and ITP. Recently, a pilot trial with the complement C5 inhibitor eculizumab indeed showed a positive effect in PLT refractory patients with anti‐HLA antibodies 28 . Theoretically, the difference with ITP could also derive from the possibility that FCGR polymorphisms in ITP do not determine so much the clearance rate of the platelets, but have an influence on the formation of the platelet‐specific autoantibodies, whereas the formation of antibodies in PLT refractoriness, which involves allo‐antigens not present in the recipient, is not influenced so much by FCGR polymorphisms.…”
Section: Resultsmentioning
confidence: 99%
“…Vo, et al, used eculizumab, a complement C5 inhibitor, to treat heavily alloimmunized patients with platelet transfusion refractoriness. Four of the 10 patients enrolled overcame platelet transfusion refractoriness with one dose of eculizumab [113]. Eculizumab has shown efficacy in warm antibody autoimmune hemolytic anemia and cold agglutinin disease [114,115].…”
Section: Treatmentmentioning
confidence: 99%
“…Therapies targeting the complement pathway are being more frequently used in immune-mediated cytopenia. Vo et al 112 used eculizumab, a complement C5 inhibitor, to treat heavily alloimmunized patients with platelet transfusion refractoriness. Four of the 10 patients enrolled overcame platelet transfusion refractoriness with 1 dose of eculizumab.…”
Section: Treatmentmentioning
confidence: 99%